The therapeutic effect of intravertebral vacuum cleft with osteoporotic vertebral compression fractures: A systematic review and meta-analysis. (April 2017) - Yu, Weibo; Liang, De; Yao, Zhensong; Qiu, Ting; Ye, Linqiang; Jiang, Xiaobing
Abstract: Background: To date, there has been ongoing debate over whether intravertebral vacuum cleft (IVC) has the effect of therapeutic efficacy in percutaneous vertebral augmentation (PVA) for the treatment of osteoporotic vertebral compression fractures (OVCFs). Objective: The aim of this meta-analysis was to calculate a pooled estimate of the IVCs on the effect of therapeutic efficacy of PVA for the treatment of OVCFs. Methods: A systematic electronic literature search was performed using the following databases: PubMed, Embase and Cochrane Library; the databases were searched from the earliest available records up to June 2016. Pooled risk ratio (RR) or a mean difference (MD) with 95% confidence interval (CI) was calculated using random- or fixed-effects models. The RevMan 5.2 was used to analyze the data. Results: In the immediate postoperative period, pooled results showed that vertebral height and VAS scores of the IVC patients were significantly lower than those of the non-IVC patients. However, pooled results showed there was no significant difference in kyphotic angle and ODI indices between the two groups. At final follow-up period, significant difference was observed in all the radiological and clinical parameters for the IVC patients with compared to the non-IVC patients in our pooled results. Pooled results showed significant difference with respect to the rate of cement leakage between the two groups. Conclusion: The IVCs had an important effect of therapeutic efficacy in PVA for the treatment OVCFs. Therefore, we strongly recommend its strict observation and follow-up for the IVCs patients. Highlights: The IVCs were very common in OVCFs. The IVCs have an important effect on therapeutic efficacy in percutaneous PVA for the treatment of OVCFs. It is important to have a strict observation and follow-up for OVCFs with IVCs after PVA.